Factors of Forming a Sense of Patriotism among Students in the Views of Eastern Thinkers - Nazarbayevich, Abduraxmanov Sherzod (Researchparks Publishing, 2023)
This article discusses the factors of formation of patriotism among students in the views of Eastern thinkers. The article discusses the importance of family and society in strengthening the sense of patriotism. Also, in the works of thinkers, opinions have been expressed about the conditions necessary for the young generation to grow up physically and spiritually.